The European digital single market strategy: Local indicators of spatial association 2011–2016. (June 2019) - Lutz, Sebastian Uljas
Abstract: This paper describes the space-time dynamics of the European digital divide. The frequencies of internet and E-commerce use are considered, along with a broad range of indicators associated with the European digital single market strategy. This paper aims to investigate the spatial structure underlying these aggregate outcome indicators. An exploratory spatial data analysis is conducted in a sample of 209 regions using Eurostat data. Strong evidence for both global and local spatial autocorrelation is found for the years 2011–2016. Consistently, a North-South polarization scheme is identified with little statistical significance in the centre of Europe. This contrasts with the high income cluster found in central Europe, while low values for digital indices and income are co-located more consistently in the South, but also in the North-East. Highlights from the specific results include: areas surrounding London as a dynamic high value cluster in E-commerce, Italy to conduct few cross-border purchases, France as a consistent adopter of E-governance, and broadband rates in general to closely reflect online activities. Highlights: High value clusters in internet and E-commerce use are found in North Europe. Local indicators show a North-South polarization in ICT use. Low adoption clusters in the North-East are sensitive to the spatial weights matrix. Regional income has similar low clusters, but high clusters are in Europe's centre. Spatial autocorrelation was present, except in ICT patents.